Pengembangan PREGA Sebagai Media Pengenalan Kewirausahaan bagi Peserta Didik SMP - Khotimah, Khusnul; I Nyoman Ruja (Jurnal Media dan Teknologi Pendidikan, 2025)
Entrepreneurship education in Indonesia has not yet received sufficient attention. In schools, it has mostly been limited to the introduction of norms or values, without reaching the level of internalization and real application in daily life. Therefore, efforts are needed to instill entrepreneurial values in students studying entrepreneurship subjects. This study developed a learning medium in the form of a board game called “PREGA” (Preneur Game). The objectives of the study were to analyze students’ needs for learning media in entrepreneurship, to evaluate the implementation of entrepreneurship learning, and to design PREGA as a learning medium. The research employed the 4-D development model consisting of four stages: define, design, develop, and disseminate. The results showed that students’ demand for entrepreneurship learning media was relatively high. Entrepreneurship material was generally delivered only theoretically, without practical application. PREGA was developed to help students understand entrepreneurship both practically and theoretically. The validation results indicated strong feasibility: material experts gave a score of 86.6% (very good, no revision needed), media experts scored 97.3%, practitioner trials scored 86%, and trials with 21 students scored 89% (very good). Based on these findings, PREGA was categorized as very good and can be implemented without revision. This suggests that PREGA has strong potential as an effective learning medium to bridge the gap between theory and practice in entrepreneurship education.